Firm characteristics and informal governance of business operations in the PRD, China - Frank Bickenbach; Wan-Hsin Liu (Kiel Institute for the World Economy (IfW), 2011)
This paper describes the Chinese economic and institutional reform process as a gradual transition of an informal, relation-based governance system into a more formal and rule-based governance system. The consequences of macro-level institutional reforms on the importance of personal relationships for the firm-level governance of business operations are discussed. Theoretical considerations based on the New Institutional Economics suggest that, in a transition economy such as China, companies' incentives to reduce the reliance on personal relationships should depend on firm characteristics such as the age, size and the internationalization of the firm. We confront these suppositions with empirical data obtained from a company survey performed among 222 (electronics industry) companies operating in the PRD, China. From this we obtain some, though often weak, evidence in favor of the suppositions.
Keywords: L20; L63; P0; 330; Formal and informal institutions; relation-based governance; firm characteristics; China; company survey; Corporate Governance; Soziale Beziehungen; Übergangswirtschaft; Institutioneller Wandel; Unternehmen; China